2020
DOI: 10.1111/fcp.12577
|View full text |Cite
|
Sign up to set email alerts
|

Ceftriaxone‐associated biliary pseudolithiasis in children: do we know enough?

Abstract: Ceftriaxone is an antibiotic agent frequently used in paediatric hospital practice for the treatment of severe bacterial infections. The use of this agent can result in cholelithiasis and/or biliary sludge, more commonly in children than in adults. This systematic review was aimed at analysing available literature concerning ceftriaxone‐associated biliary pseudolithiasis in paediatric patients, with a special emphasis on the clinical aspects. A literature analysis was performed using Medline and Embase electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 61 publications
(83 reference statements)
0
17
0
2
Order By: Relevance
“…In our three cases, only one risk factor, which was noticed in our case, is a high dose of ceftriaxone along with a prolonged duration of more than three weeks to four months. Palanduz, et al [11] reported in their study that 118 children were admitted to hospital for severe infection and received intravenous ceftriaxone at a dose of 100 mg/kg /day for three weeks. On days one, seven, and fourteen, an ultrasound abdomen was performed at regular intervals to monitor the adverse effects of ceftriaxone.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…In our three cases, only one risk factor, which was noticed in our case, is a high dose of ceftriaxone along with a prolonged duration of more than three weeks to four months. Palanduz, et al [11] reported in their study that 118 children were admitted to hospital for severe infection and received intravenous ceftriaxone at a dose of 100 mg/kg /day for three weeks. On days one, seven, and fourteen, an ultrasound abdomen was performed at regular intervals to monitor the adverse effects of ceftriaxone.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…В качестве примера можно привести цефтриаксон-ассоциированный билиарный псевдолитиаз у детей. После применения цефтриаксона в течение некоторого продолжительного периода у 17% детей возможно сгущение желчи в виде осадка желчного пузыря без акустической тени по данным ультразвукового метода исследования органов брюшной полости [5]. Восстановление сонографической картины желчного пузыря и реологии желчи происходит после отмены цефтриаксона в течение нескольких недель.…”
Section: внешние факторыunclassified
“…2 Most reports of pseudolithiasis involve high doses of the drug being administered to children. 3 There are still few reports of pseudolithiasis in older adults. 4 We herein report an older patient in whom biliary pseudolithiasis occurred as a result of administering a loading dose of lascufloxacin (LSFX).…”
Section: Biliary Pseudolithiasis In An Older Patient Treated With Lascufloxacinmentioning
confidence: 99%
“…It is also used to treat stress incontinence in the elderly. [1][2][3] In Japan, the press-through-package (PTP) sheets and the shape of the tablets of clenbuterol hydrochloride resemble those of galantamine. Hence, elderly patients with dementia and stress incontinence can mistake one drug for the other or mix them up, which could result in drug poisoning.…”
Section: Disclosure Statementmentioning
confidence: 99%